(untitled) (Global Journal of Medical Research, 2018)
Multiple myeloma is a haematogical malignancy caused by abnormality of plasma cells characterized by (a) hypercalcemia, (b) renal insufficiency or failure, (c)bone pain and abnormal bone radiographs, (d) anemia and (e) a monoclonal protein in urine or serum or both. It begins in the form known as monoclonal gammopathy of undetermined significance (MGUS) and progresses to asymptomatic myeloma and then lastly to symptomatic myeloma. The three main domains in the understanding of Pathophysiology are cytokines and cell signaling, bone Marrow Microenvironment and cell Cycle. Bifunctional alkylating agents like Melphalan and cyclophosphamide are considered as standard therapy for multiple myeloma. Patients who are chosen for stem cell transplantation can be treated with Lenalidomide, an immunomodulatory agent and an aminosustituted variant of Thalidomide. It is given along with dexamethas one. In stem cell therapy, the patients receive stem cells intravenously similar to the blood transfusion and this phase takes 1-5 hours. After entering the blood stream through a process called engraftment, the stem cell produce new WBCs, RBCs and platelets. The immune rejection of donor cells by the host immune system is a major drawback of transplantation. Stem cell therapy in multiple myeloma is very effective and should be opted as one among the best for both older patients and patients younger than 65 years.